2012
DOI: 10.4049/jimmunol.1103430
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Produced by the NADPH Oxidase 2 Complex in Monocytes Protect Mice from Bacterial Infections

Abstract: Chronic granulomatous disease (CGD) is an inherited disorder characterized by recurrent life-threatening bacterial and fungal infections. CGD results from defective production of reactive oxygen species by phagocytes caused by mutations in genes encoding the NADPH oxidase 2 (NOX2) complex subunits. Mice with a spontaneous mutation in Ncf1, which encodes the NCF1 (p47phox) subunit of NOX2, have defective phagocyte NOX2 activity. These mice occasionally develop local spontaneous infections by Staphylococcus xylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 51 publications
6
84
0
Order By: Relevance
“…Thus, calpain KO macrophages and neutrophils failed to mount comparable ROS production to WT control cells, which may explain the delayed bacterial killing we observed. Indeed, ROS production by NADPH oxidase 2 (NOX2) is required to protect mice from spontaneous and recurrent bacterial infections [61]. Our results are also in agreement with a recent study that showed calpain inhibitors dampen ROS production in neutrophils treated with .…”
Section: Discussionsupporting
confidence: 82%
“…Thus, calpain KO macrophages and neutrophils failed to mount comparable ROS production to WT control cells, which may explain the delayed bacterial killing we observed. Indeed, ROS production by NADPH oxidase 2 (NOX2) is required to protect mice from spontaneous and recurrent bacterial infections [61]. Our results are also in agreement with a recent study that showed calpain inhibitors dampen ROS production in neutrophils treated with .…”
Section: Discussionsupporting
confidence: 82%
“…A mutation in the Ncf1 gene (m1j) (the Ncf1 protein also denoted p47phox) in the B10Q mice, designated as B10Q.Ncf1 m1j/m1j , impairs the expression of the Ncf1 gene, thereby totally blocking the function of the NOX2 complexes, as described earlier (15,18). The B10Q.Ncf1 m1j//m1j .MN + strain has a transgene expressing functional Ncf1 on macrophages using the human CD68 promotor (22,57). This transgene is used when expressed heterozygously, and MN − mice are B10Q.Ncf m1j//m1j littermate controls.…”
Section: Methodsmentioning
confidence: 99%
“…AT1Rs are involved in the cerebrovascular dysfunction induced by ANGII (10). Macrophages are well known to express AT1R and produce ROS in response to ANGII (23,24). Therefore, we sought to determine whether AT1Rs on PVMs participate in the cerebrovascular effects of ANGII.…”
Section: Perivascular Macrophages Mediate the Neurovascular And Cognimentioning
confidence: 99%
“…As the vessels penetrate deeper into the substance of the brain, the glial and vascular basement membranes fuse together and the perivascular space disappears (22). As macrophages, PVMs express AT1Rs and have the potential to produce large amounts of ROS through NOX2 (23,24). To provide more direct evidence that blood-borne ANGII reaches the perivascular space in proximity to PVMs, we administered biotinylated ANGII i.v.…”
Section: Perivascular Macrophages Mediate the Neurovascular And Cognimentioning
confidence: 99%